2000
DOI: 10.18388/abp.2000_3992
|View full text |Cite
|
Sign up to set email alerts
|

Cellular aspects of folate and antifolate membrane transport.

Abstract: Folates--one carbon carriers--take part in the metabolism of purine, thymidylate and some amino acids. Internalization of these compounds employs several mechanisms of transport systems. Reduced folate carriers and folate receptors play the most important role in this process. The physiological role of these molecules in normal and neoplastic cells is described regarding changes in transport activity and connection of transport systems with resistance to antifolates and cancer development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 75 publications
0
32
0
Order By: Relevance
“…Folate: Dietary folates exist mainly in polyglutamate forms, which must be deconjugated, through hydrolysis, to the monoglutamyl form before absorption. This occurs in the intestine and is accomplished by the folylpoly-γ-glutamate carboxypeptidase (FGCP) (Brzezinska et al 2000). Subsequently, folate monoglutamates are absorbed and reach the bloodstream.…”
Section: The Role Of B Vitamins In Homocysteine Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Folate: Dietary folates exist mainly in polyglutamate forms, which must be deconjugated, through hydrolysis, to the monoglutamyl form before absorption. This occurs in the intestine and is accomplished by the folylpoly-γ-glutamate carboxypeptidase (FGCP) (Brzezinska et al 2000). Subsequently, folate monoglutamates are absorbed and reach the bloodstream.…”
Section: The Role Of B Vitamins In Homocysteine Metabolismmentioning
confidence: 99%
“…5-MethylTHF monoglutamate is the principal circulating form of folate, and is transported across the cell membranes. The highest cellular uptake of folate, including its absorption in the intestine, occurs via a specialized membrane carrier system identified as the reduced folate carrier (RFC) (Brzezinska et al 2000). This carrier is ubiquitously expressed and preferentially transports 5-methylTHF (Maddox et al 2003;Whetstine et al 2002;Wong et al 1995).…”
Section: The Role Of B Vitamins In Homocysteine Metabolismmentioning
confidence: 99%
“…In the present study, we have demonstrated the mechanistic insights of the regulation of folate transport systems in HepG2 cells in conditions of alcoholism and folate deficiency. These results are important in the view of the fact because folate availability is an important determinant of the activities of the transport system [35,36]. Furthermore, the studies on the mechanism of regulation of folate transport via the transport proteins like the PCFT, RFC, and FR are of considerable importance in context of the antifolate resistance and subsequently in the novel drug delivery systems exploiting such routes.…”
Section: Discussionmentioning
confidence: 99%
“…Thiazole derivatives are associated with a broad spectrum of biological properties, such as anticonvulsant, [4] antimicrobial, [4,5] antitubercular, [6] antiviral, [7] antimalarial, [8,9] anticancer, [10] antihypertensive, [11] anti-inflammatory, [12] and anti-allergic. [13] Thiazole derivatives also find application in various fields, including photonucleases, [14] polymers, [15] liquid crystals, [16] fluo-rescent dyes [17,18] or intermediates for dyes, [19] insecticides, [20,21] plant protectants, [22] antioxidants, [23] vulcanising accelerators (mercaptobenzothiazole), [24] and photosensitizers. [25] As a continuation of our interest in the synthesis of functionalized 2-aminothiazoles possessing antimicrobial activity, [26][27][28][29] herein we report the synthesis of novel variously functionalized thiazole derivatives and screening of their antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%